TWO SIDES OF THE SAME COIN: AN E-COMMERCE ECOSYSTEM AGENT-BASED SIMULATION - Strobel, Gero; Wulfert, Tobias; Banh, Leonardo (Wirtschaftsinformatik 2024 Proceedings, 2024)
E-commerce is one of the most important sectors of the economy, with an expected global turnover of USD 7.4 trillion in 2024. Leading companies in the industry like Amazon and Alibaba leverage platform business models that orchestrate complex ecosystems of buyers and sellers. These ecosystems are characterized by globally intertwined networks of independent participants and multifaceted interactions, making their development hard to predict. We propose an agent-based simulation approach, following the three-step process of Haki et al. (2020), to predict the behavior of e-commerce ecosystems with a particular focus on the impact of premium subscription services. Simulation models offer the opportunity to tangibly visualize the effects of a participant's actions on the ecosystem level. Our simulation includes the key actors (i.e., buyer, seller, marketplace), their characteristics, and behaviors to draw conclusions about the evolution of the ecosystem and the strategic role of premium memberships in shaping these digital landscapes.
Keywords: E-Commerce Ecosystem; Agent-Based Simulation; Computationally Intensive Theory Construction